Resilience, Restoration, and Sustainability: Revisiting the Fundamental Principles of the Clean Water Act - Robert W. Adler (Washington University Journal of Law & Policy, 2010)
Some of the major underpinnings of the Clean Water Act ("CWA") merit reconsideration given changes in science and society. Any attempt at such a sweeping analysis of a statute that spans hundreds of pages of text would necessarily be incomplete, especially in a relatively short symposium essay. Therefore, I am taking a thematic approach based on the guiding principles Congress articulated in the law‘s opening provision: "The objective of this chapter is to restore and maintain the chemical, physical, and biological integrity of the Nation‘s waters." From this overarching statement of the statutory goals, I will critique four major concepts. First, the concept of "integrity" was adopted and has been interpreted based on ecological concepts that have evolved considerably over time; today, there is greater recognition of the understanding that healthy ecosystems are evolutionary rather than static. In Part I, I address the need to move from a focus on ecological stability or equilibrium to an emphasis on ecological health and resilience of the nation‘s waters. Second, although the text says "restore and maintain," the concept of restoration is unfortunately narrow in practice, in part due to limitations in the operative provisions of the law itself and in part due to the historically narrow focus of statutory implementation. In Part II, I propose a relative shift in focus from maintenance to restoration. Third, although Congress clearly recognized in 1972 that runoff from agriculture and other intensive land use contributes as significantly to water pollution as do discharges from municipal and industrial point sources, the operative provisions of the law were written—and certainly have been implemented—mainly with the latter in mind. In Part III, I suggest a shift in focus appropriate to the transition from an industrial to a post-industrial age. Finally, although Congress expressed a clear intent in 1972 to expand the scope of federal water pollution control efforts to the full extent permissible under the Constitution, its definition of the "waters of the United States" retained a reference to navigation, which the Supreme Court has interpreted as limiting the scope of the statute in some significant respects. In Part IV, I support efforts to expand the jurisdictional focus of the Act from navigable waters to sustainable waters, to better match the breadth of Congress's constitutional authority, and to better fulfill the statutory focus on watershed and ecosystem health.
Keywords: Restoration ecology; Water -- Law & legislation; Sustainable development; Water pollution; United States. Environmental Protection Agency; Aquatic ecosystems; Water conservation; Water pollution control; Clean Water Act of 1977